2009
DOI: 10.1021/ol901806q
|View full text |Cite
|
Sign up to set email alerts
|

Thiadiazole Fused Indolo[2,3-a]carbazole Based Oligomers and Polymer

Abstract: Indolo[2,3-a]carbazole-based heteroacenes containing thiadiazole units were synthesized. Compounds showed a sandwich herringbone packing in solid state with improved stability. The change in photophysical and electrochemical properties upon incorporation of an acceptor moiety (benzothiadazole) in a fused ring system was studied. The unsubstituted compound was electropolymerized to yield a stable polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…[58] The more anodic value found for ( [67] Polymerization of (2,1-a)-IF is also observed along oxidation at fixed potential. For example, a deposit prepared by oxidation at 2 V for 180 s, removed from the electrolyte, rinsed in dichloromethane and studied in a new "monomer free" solution, presents the profile shown in Figure [25,75] In addition, poly-(2,1-a)-IF appears stable in a wide potential range, that is, between 0.67 and 2.4 V. Poly-(2,1-a)-IF is hence highly more stable than structurally related electrogenerated polymer such as poly-(1,2-b)-indenofuorene, poly-(1,2-b)-IF [67] or poly-fluorene, poly(F). [76] Indeed, poly-(1,2-b)-IF and poly(F) present stable p-doping processes between 0.75 and 1.76 V and between 0.97 and 1.5 V, respectively.…”
Section: A C H T U N G T R E N N U N Gmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] The more anodic value found for ( [67] Polymerization of (2,1-a)-IF is also observed along oxidation at fixed potential. For example, a deposit prepared by oxidation at 2 V for 180 s, removed from the electrolyte, rinsed in dichloromethane and studied in a new "monomer free" solution, presents the profile shown in Figure [25,75] In addition, poly-(2,1-a)-IF appears stable in a wide potential range, that is, between 0.67 and 2.4 V. Poly-(2,1-a)-IF is hence highly more stable than structurally related electrogenerated polymer such as poly-(1,2-b)-indenofuorene, poly-(1,2-b)-IF [67] or poly-fluorene, poly(F). [76] Indeed, poly-(1,2-b)-IF and poly(F) present stable p-doping processes between 0.75 and 1.76 V and between 0.97 and 1.5 V, respectively.…”
Section: A C H T U N G T R E N N U N Gmentioning
confidence: 99%
“…This onset potential difference between poly-(2,1-a)-IF and (2,1-a)-IF is consistent with an extended p-conjugation in poly-(2,1-a)-IF as previously observed for other electrogenerated p-conjugated polymers. [25,75] In addition, poly-(2,1-a)-IF appears stable in a wide potential range, that is, between 0.67 and 2.4 V. Poly-(2,1-a)-IF is hence highly more stable than structurally related electrogenerated polymer such as poly-(1,2-b)-indenofuorene, poly-(1,2-b)-IF [67] or poly-fluorene, poly(F). [76] Indeed, poly-(1,2-b)-IF and poly(F) present stable p-doping processes between 0.75 and 1.76 V and between 0.97 and 1.5 V, respectively.…”
Section: Synthesismentioning
confidence: 99%
“…[ 12 ] Balaji et al reported the synthesis and electrochemical polymerization of thiadiazole fused IC derivatives ( 1 ). [ 13 ] The thiadiazole‐fused ICs were further modified with different substituents and fused rings. [ 14–16 ] Thiadiazole‐fused ICs have been successfully incorporated into the conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…6-Bromo-4H-thieno[3,2-b]indole was synthesized according to the procedure of Dong and co-workers (Yang et al, 2017). Referring to the synthesis of indolocarbazole derivatives (Kato et al, 2012;Balaji et al, 2009), we designed a synthetic route (Fig. 2) and the detailed synthesis procedure of TIP is described below.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%